Development and characterization of moringa oleifera fruit waste pod derived particulate cellulosic reinforced epoxy bio-composites for structural applications. Issue 6 (June 2022) - Oladele, Isiaka Oluwole; Ogunwande, Gabriel Seun; Taiwo, Anuoluwapo Samuel; Lephuthing, Senzeni Sipho
Abstract: The desire for environment-friendly materials and sustainability has brought a paradigm shift in the way engineers and the entire material research community thinks while attempting to develop new material, particularly for engineering applications. This study is carried out to underscore the suitability of particulate moringa oleifera fruit pod (MOFP) reinforced epoxy bio-composites on selected properties for structural applications. The dried waste fruit pods were processed as calcined and pulverized fruit pod particulates, respectively. Their respective bio-composites were developed by blending the selected materials in predetermined proportions using the open mould processing method. The MOFP particles were characterized with SEM/EDS and XRD while mechanical and wear properties of the developed bio-composites were evaluated. The results showed that the pulverized MOFP reinforced epoxy bio-composites showed improved properties than the calcined MOFP bio-composites in most of the properties considered. This was noticed to be due to the presence of more elemental constituents and at higher proportions in pulverized particles than in the calcined particles. It was discovered that 15 wt.% pulverized MOFP reinforced epoxy bio-composites gave about 67.9%, 28.7%, 8.8%, and 8.8% enhancement and with a value of 70.2 HS, 39.02 MPa, 198.4 MPa, and 753.28 MPa in hardness, flexural strength, flexural modulus, and tensile modulus, respectively to emerge as the reinforcement content with the optima properties. Based on the findings, MOFP particles reinforced epoxy-based biocomposites can be used in applications where stiffness and high strength are not essential requirements; packaging applications; in electrical component applications such as circuit boards, and cables due to their low thermal conductivity. Abstract : moringa fruit pod; environmental concern; eco-friendly; epoxy bio-composites; green material; structural application